Tarqiyah Maharat al-Qarn al-Hadi wa al-‘Isyrin fi Ta’lim Maharah al-Kalam ‘ala Asas al-Ta’lim al-Bina’i fi al-Jami’ah - Rosikh, Fahrur; Rohman, M. Fathor; Finurika, Isna; Nisa’, Khoirun (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This study aimed to analyze the development of 21st century skills in the learning of constructivism-based speaking skill at Pesantren sunan drajat Lamongan. The research method used was qualitative research with the type of explanatory case study. Data collection techniques deployed observation, interviews, and documentation. The data analysis techniques consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicated that constructivism-based speaking skill learning could develop students' 21st century skills. The developed 21st century skills included the skills of critical thinking, creative thinking, collaboration, and communication. Critical thinking skills were reflected in the abilities to analyze materials and learning resources, to find social facts, to choose mufrodat used in socio-drama practice, and to use Arabic grammar. Creative thinking skills were reflected in the abilities to compose drama scripts, to design drama scenarios, and to utilize the media in drama practice. Collaboration skills were reflected in the abilities to cooperate in observation activities, to cooperate in composing drama scripts, and to cooperate in drama training and practice. Lastly, communication skills were reflected in the abilities to express ideas, thoughts and feelings in Arabic, to carry out dialogues in Arabic, and to pronounce Arabic words and sentences correctly and correctly.